Does Infant Reactivity Moderate the Association Between Antenatal Maternal Depression and Infant Sleep?. Issue 6 (July 2015) - Netsi, Elena; van IJzendoorn, Marinus H.; Bakermans-Kranenburg, Marian J.; Wulff, Katharina; Jansen, Pauline W.; Jaddoe, Vincent W. V.; Verhulst, Frank C.; Tiemeier, Henning; Ramchandani, Paul G.
ABSTRACT: Objective: A number of studies have established an association between antenatal maternal depression and infant sleep. One key question is whether all infants are equally susceptible to environmental influences, including the intrauterine environment. Reactive temperament has been examined as a plasticity factor, with accumulating evidence suggesting that infants with reactive temperament may be more susceptible to both positive and negative environmental influences. This study examines whether infant reactivity moderates any association between antenatal depression and infant sleep in 2 longitudinal studies: the Avon Longitudinal Study of Parents and Children (ALSPAC) and Generation R cohorts. Methods: Maternal depression scores were assessed during pregnancy using Edinburgh Postnatal Depression Scale and Brief Symptom Inventory. Infant sleep duration and awakenings, in ALSPAC (N = 8318) and Generation R (N = 2241), were assessed at 18 and 24 months of age, respectively. Infant reactivity was assessed by temperament questionnaire at 6 months of age. Results: Hierarchical linear regression models indicated a 3-way interaction between reactivity and gender moderating the effect of antenatal depression on infant sleep, on sleep duration in Generation R at 24 months (β = .085, p < .001) in the whole sample and when limited to the Dutch/European group (β = .055, p = .030), and on night awakenings at 18 months in ALSPAC (β = −.085, p = .013). Boys with more reactive temperament exhibited shorter sleep duration and a higher number of awakenings when previously exposed to maternal symptoms of antenatal depression. Conclusion: For the first time, these findings highlight, in 2 large cohorts, that children with temperamental reactivity may be more vulnerable to antenatal depression, raising the possibility of targeted interventions to improve infant outcomes. Abstract : This article has supplementary material on the web site: www.jdbp.org.